Penggunaan Media Pembelajaran Happy Note dalam Meningkatkan Minat Belajar Pendidikan Agama Islam Siswa Kelas 1 SDN 003 Bontang Utara Tahun Pelajaran 2024/2025 - Ningsih, Fitri; Murni, Murni (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
Abstract -  Education is an effort to prepare the nation's younger generation to face the global era. Therefore, to provide effective education, it is essential to ensure quality learning that enhances human resource development through appropriate approaches and learning outcomes, both of which are inseparable from the learning process. Considering the importance of Islamic Religious Education at the elementary school level, special attention is needed to increase students' learning interest—particularly in this subject—in order to create a more creative and innovative learning process and to improve students' overall academic achievement.. This thesis discusses the use of Happy Note learning media in increasing the interest in learning Islamic Religious Education among first-grade students at SDN 003 Bontang Utara. The purpose of this research is to describe the implementation of Happy Note as a learning medium and to examine how its use can enhance students' interest in learning Islamic Religious Education. This study employs a qualitative research approach. The research subjects are first-grade students at SDN 003 North Bontang. Data were collected using triangulation methods, including interviews, observations, and documentation. The data were analyzed through data reduction, data presentation, and drawing conclusions. The research findings show that the use of Happy Note learning media (1) can increase students' interest in learning Islamic Religious Education, (2) brings a new and engaging atmosphere to the learning process, and (3) enhances student motivation and enthusiasm. This learning medium proves to be effective in fostering interest in Islamic Religious Education. It can be concluded that the use of Happy Note media has a positive impact and contributes to making the learning process more effective and enjoyable, thereby increasing first-grade students' interest in Islamic Religious Education.